Communicating Social Capitals of Local Communities for a Sustainable Proklim in Aceh - Rizanna Rosemary; Safrina; Nellyana Roesa (Fakultas Ilmu Komunikasi Universitas Pancasila, 2022)
Program Kampung Iklim (Proklim) is a national mitigation and adaptation program to climate change in Indonesia. Like other areas across the country, several districts in Aceh Province are designated Climate Village Program (Proklim). However, as an innovative government-led initiative, the program's efficacy in Aceh has not been well-documented. This study explores the potential challenges and opportunities of Proklim implementation in Aceh. Even though Proklim is a significant initiative for adapting to the impact of climate change, poor community involvement in the planning and implementation stages led to the program's unsustainability. Lack of public participation correlates with their limited understanding of the program's benefits. Moreover, people's poor understanding is influenced by how the program is communicated. Drawing from previous research on public participation in implementing Proklim in three areas in Aceh Besar districts, this study analyzes the internal and external factors identified as strengths, weaknesses, opportunities, and threats of the climate change programs. The study argues that exploring and communicating the social capitals of local communities allows for more public involvement and participation in developing sustainable Proklim in the area.